The Welsh Language - Janet Davies (University of Wales Press, 2014)
For many people in Wales, the Welsh language is the essence of Welsh identity. Yet, for the majority of the people of Wales, the language has only a marginal impact upon their lives. That was my experience as a child. I was brought up on the borders of Breconshire and Monmouthshire, a district where a considerable number of the inhabitants had a knowledge of Welsh a hundred years ago. By the 1950s, however, none of the native inhabitants could put together a sentence in the language. A few incomers were Welsh speakers, a fact that sometimes impinged upon us. Our parish church was Llanelly, magnificently sited above the Usk valley. Its vicar was Daniel Parry- Jones, a native of Carmarthenshire, and the first Welsh I ever heard came from his lips as he proffered the communion cup to the distinguished Irishwoman, Dr NoÃ«lle French. Welsh, I came to the conclusion, was a liturgical language, rather like Latin among Roman Catholics. There were Welsh lessons at school, but it was difficult to imagine that anyone of my age could weave together the words we learned and turn them into intelligible and effortless speech. That some of my contemporaries could do so was something I discovered when pupils from Brynmawr met pupils from Ystradgynlais, at that time in the same county. Thus I became dimly aware that somewhere over the hills, in the upper Swansea valley, in Carmarthenshire, and also, according to some, in Anglesey,there were people who not only spoke Welsh effortlessly, but did so all the time. It seemed very odd indeed.